Change in MRI-detected subchondral bone marrow lesions is associated with cartilage loss: the MOST Study. A longitudinal multicentre study of knee osteoarthritis. - Roemer, F; Guermazi, A; Javaid, M; Lynch, J; Niu, J; Zhang, Y; Felson, D; Lewis, C; Torner, J; Nevitt, M (2009)
OBJECTIVES: To describe the natural history of subchondral bone marrow lesions (BMLs) in a sample of subjects with knee osteoarthritis (OA) or at risk of developing it. Additionally, to examine the association of change in BMLs from baseline to 30-month follow-up with the risk of cartilage loss in the same subregion at follow-up. METHODS: 1.0 T MRI was performed using proton density-weighted, fat-suppressed sequences. BML size and cartilage status were scored in the same subregions according to the WORMS system. Subregions were categorised based on comparison of baseline and follow-up BML status. A logistic regression model was used to assess the association of change in BML status with cartilage loss over 30 months using stable BMLs as the reference group. RESULTS: 395 knees were included. 66% of prevalent BMLs changed in size; 50% showed either regression or resolution at follow-up. The adjusted odds ratios (95% confidence intervals) of cartilage loss in the same subregion at follow-up for the different groups were 1.2 (0.5 to 1.6) for regressing BMLs, 0.9 (0.5 to 1.6) for resolving BMLs, 2.8 (1.5 to 5.2) for progressing BMLs, 0.2 (0.1 to 0.3) for subregions with no BMLs at baseline and follow-up and 3.5 (2.1 to 5.9) for newly developing BMLs. BML size at baseline was associated with risk of subsequent cartilage loss. CONCLUSIONS: The majority of pre-existing BMLs decreased in size at follow-up. Absence of BMLs was associated with a decreased risk of cartilage loss, while progressing and new BMLs showed a high risk of cartilage loss in the same subregion.